A new species of Amorphophallus (Araceae—Thomsoniaea) from Sulawesi, Indonesia - Yuzammi, Yuzammi; Hetterscheid, Wilbert (Phytotaxa, 2020)
Amorphophallus ardii is described and illustrated, and compared to other Indonesian Amorphophallus species. The species was collected in the Matarombeo limestone mountain range in Southeast Sulawesi, Indonesia. The species is restricted to karst areas and endemic to Southeast Sulawesi.